2014
DOI: 10.1159/000368664
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Molecular Analyses of XY Ovaries from the African Pygmy Mouse <b><i>Mus minutoides</i></b>

Abstract: The African pygmy mouse Mus minutoides is characterized by the presence of a high proportion of fertile XY females in natural populations. This species displays 2 morphologically different X chromosomes: the ancestral X and a shorter one designated as X*, feminizing the X*Y individuals. This strongly suggests that in the presence of an X* chromosome, the male differentiation program is not activated despite a functional Y chromosome. In this study, we compared the histology of the adult ovaries of the 3 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…During the last decade, there has been a growing interest in the ”direct” role of the expression of sex chromosome genes on the shaping of sexual dimorphic behaviours 7 , as opposed to the “indirect” way: trough the action of gonadal hormones 53 . In the African pygmy mouse, the lack of noticeable differences between the anatomy and ovaries of XX, XX* and X*Y females 23 could imply that all female have similar levels of circulating gonadal hormones (though this would have to be confirmed by hormonal assay). So the differences found in this study in terms of aggressiveness, anxiogenous response to novelty and exploratory behaviour is likely to result from the direct influence of genes of the Y, X and X* chromosomes on the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decade, there has been a growing interest in the ”direct” role of the expression of sex chromosome genes on the shaping of sexual dimorphic behaviours 7 , as opposed to the “indirect” way: trough the action of gonadal hormones 53 . In the African pygmy mouse, the lack of noticeable differences between the anatomy and ovaries of XX, XX* and X*Y females 23 could imply that all female have similar levels of circulating gonadal hormones (though this would have to be confirmed by hormonal assay). So the differences found in this study in terms of aggressiveness, anxiogenous response to novelty and exploratory behaviour is likely to result from the direct influence of genes of the Y, X and X* chromosomes on the brain.…”
Section: Discussionmentioning
confidence: 99%
“…These genes, and others of the non-recombining region of the Y, could be responsible for differences in anxiogenic response to novelty, locomotor activity and number of aggressions which dissociate Y chromosome bearers (X*Y and XY) from non-bearers (XX and XX*) in the pygmy mouse. Sry is a serious candidate, as it has been shown to be strongly expressed in the brain of X*Y females in the pygmy mouse 23 . In regard to attack latency, X*Y female differ from the XX, and XX* are intermediate, evoking an influence of the X*.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although limited investigation seemed to suggest random X inactivation of either the X or X* in XX* females (H. Winking, personal communication, in Schempp et al (1985)), other results showed more striking patterns, with complete nonrandom X or X* inactivation (100%) in specimens with numerically aberrant X*XY sex chromosome constitution (Schempp et al 1985). Recently, a novel case of unusual mammalian sex determination system was described in the African pygmy mouse, Mus minutoides, a close relative of the house mouse (Veyrunes et al 2010;Rahmoun et al 2014;Zhao et al 2017). In wild populations, up to 75% of females carry a Y chromosome and a peculiar feminizing X* chromosome and are fully fertile.…”
Section: Introductionmentioning
confidence: 99%
“…An atypical sex determination system has been described in the African pygmy mouse Mus minutoides . In this species, regular XX females and XY males exist, but in addition, individuals bearing a normal Y and a variant X (X*) develop as females, despite the presence of the Y chromosome and Sry 12 13 . While the genetic variation that allows the X* to override the male sex-determining programme has not been identified, the other side of the coin is the question of whether the male sex-determining pathway has been weakened in this species, perhaps rendering it vulnerable to be overridden by X*.…”
mentioning
confidence: 99%